2009
DOI: 10.1111/j.1601-5223.1972.tb01376.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytology of the Elymus (Agropyron) elongatus complex

Abstract: The taxa cytologically studied in the Elymus (Agropyron) elongatus complex included three subspecies of E. elongatus, i.e., ssp. elongatus and ssp. haifensis (2n= 14) and ssp. flaccidi‐folius (2n = 28), as well as E. varnensis (2n = 70). A brief taxonomic treatment of these different types is presented. Differences in karyotype were observed between materials of ssp. elongatus that have different origin as well as between ssp. elongatus and ssp. haifensis. Both subspecies have heteromorphic chromosome pairs. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Beauv. ], exhibit exclusive or almost exclusive bivalent pairing at meiosis in spite of the fact that originally they contained two or more homologous genomes [96][97][98]. The cytologically diploidized autopolyploids, being more fertile than the typical ones, are prevalent among annual species.…”
Section: Genome Size In Autopolyploidsmentioning
confidence: 99%
“…Beauv. ], exhibit exclusive or almost exclusive bivalent pairing at meiosis in spite of the fact that originally they contained two or more homologous genomes [96][97][98]. The cytologically diploidized autopolyploids, being more fertile than the typical ones, are prevalent among annual species.…”
Section: Genome Size In Autopolyploidsmentioning
confidence: 99%
“…This autopolyploid origin of the tetraploid Th. elongatum was also characterized by the occasional formation of quadrivalents at meiosis (Heneen & Runemark, 1972). A high level of pairing was exhibited by the triploid hybrids between the natural tetraploid and diploid cytotypes, 4.15 bivalents and 2.82 trivalents per cell, also supporting the assumption that the natural tetraploid is of an autoploid origin (Charpentier et al., 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The species Thinopyrum elongatum is composed of diploid (2 n = 2 x = 14), tetraploid (2 n = 4 x = 28) and decaploid (2 n = 10 x = 70) cytotypes. From its karyotype and gross morphology, it was concluded that the tetraploid was an autotetraploid, with two genomes undergoing some differentiation (Breton‐Sintes & Cauderon, 1978; Heneen & Runemark, 1972). This finding was further supported by the degree and pattern of chromosome pairing in F 1 triploid hybrids between the two cytotypes (Dvořák, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…As a perennial plant, Thinopyron elongate presents significant features of resistance to drought and diseases. The chromosome complement of it was named as EE, there are diploid (EE), tetraploid (E1E1E2E2), and decaploid (EE1E2E4E5) according to cytological classification [6,7] . In Thinopyron elongate, the study on karyotype and banding was started later because of the technical limitation in Thinopyron, in which chromosomes showed less bands by conventional staining method used for wheat.…”
Section: Introductionmentioning
confidence: 99%